(untitled) (Historia, 2021)
Neither Sandhurst, nor West Point: the South African Military Academy and its foreign role models The South African Military Academy was established on 1 April 1950 with a view to placing officer training in the Union Defence Force on par with international standards; and, specifically, is was to be tailored to the West Point and Sandhurst models. Yet when established, the Academy was completely subservient to its guardians - the University of Pretoria and the SA Military College - and the cadets received an almost purely civilian academic education. Therefore neither in terms of status and atmosphere nor military-academic content was it on par with either West Point or Sandhurst. During the mid-1950s, drawing on the Indian National Defence Academy, Defence Headquarters re-established the Academy as an independent, tri-service academy at Saldanha under the University of Stellenbosch. Yet, conducting very little military training, the Academy still bore only a superficial resemblance to the foreign role models. Only from 1970 was the formative training of all permanent force officers entrusted to the Academy and every effort made to tailor its training programme closely to foreign counterparts, and to West Point and the Dutch military academy at Breda in particular. However, the formative training of candidate officers was returned to the services in 1976, whilst commissioned officers, instead of candidate officers only, were also admitted to the Academy from that date with the result that the Academy became a military university rather than a military academy.